2015
DOI: 10.1111/ggi.12448
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term effects of exercise and amino acid supplementation on muscle mass, physical function and falls in community‐dwelling elderly Japanese sarcopenic women: A 4‐year follow‐up study

Abstract: Participation in an intervention could prevent significant declines in lower extremity muscle mass, strength and mobility, even in the long-term, and might be beneficial in suppressing otherwise significant rises in fall rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 29 publications
0
17
0
2
Order By: Relevance
“…As well as exercises, nutritional interventions are proved to be important aspects. There are several studies that showed the additive effects of supplementation with protein [ 56 , 57 ], amino acids [ 58 ] to exercise intervention.…”
Section: Prevention Of the Onset And Progression Of Lsmentioning
confidence: 99%
“…As well as exercises, nutritional interventions are proved to be important aspects. There are several studies that showed the additive effects of supplementation with protein [ 56 , 57 ], amino acids [ 58 ] to exercise intervention.…”
Section: Prevention Of the Onset And Progression Of Lsmentioning
confidence: 99%
“…These two studies were therefore included in the final analyses. Nine studies used retrospective falls data collection methods rather than the gold standard prospective falls diary method [8,9,15,16,[21][22][23][24][25]. A post hoc sensitivity analysis was undertaken to explore impact on falls rate; exclusion of these nine studies did not change the magnitude of the effect estimate, therefore, all studies were included in the meta-analysis.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…In industrialised countries, physical activity levels in older adults are low, with 40-60% of the older adults not meeting the recommendations for physical activity [8,9]. Although exercise has been proved to be effective in reversing losses of muscle mass [6,10], studies investigating the effect of general physical activity on the prevention of sarcopenia show inconsistent results [11]. For example, Ryu et al, using data from a cross-sectional Korea National Health and Nutrition Examination Survey, report that moderate-vigorous physical activity (MVPA) is associated with a reduced risk of sarcopenia [12].…”
Section: Introductionmentioning
confidence: 99%